2012
DOI: 10.1111/j.1939-1676.2012.00914.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy and Safety of High Dose Short Duration Enrofloxacin Treatment Regimen for Uncomplicated Urinary Tract Infections in Dogs

Abstract: BackgroundUncomplicated urinary tract infections (UTI) in dogs usually are treated with antimicrobial drugs for 10–14 days. Shorter duration antimicrobial regimens have been evaluated in human patients.HypothesisA high dose short duration (HDSD) enrofloxacin protocol administered to dogs with uncomplicated UTI will not be inferior to a 14-day treatment regimen with amoxicillin-clavulanic acid.AnimalsClient-owned adult, otherwise healthy dogs with aerobic bacterial urine culture yielding ≥103 CFU/mL of bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 28 publications
0
47
1
2
Order By: Relevance
“…In the current study, the data on clinical remission parameters (Table 3) indicate that a single dose of ceftriaxone administration is superior to multiple doses of enrofloxacine for 14 days. Although 91.4% and 93.9% of uropathogens from dogs with uncomplicated urinary tract infections were susceptible to enrofloxacine and amoxicillin, respectively, the rate of clinical cure in response to the administration of these agents was lower than the values from susceptibility test (Westropp et al 2012). In this study, isolated uropathogens were sensitive to both enrofloxacine and ceftriaxone with no significant differences identified between clinical and microbiological cures.…”
Section: Pre-treatment Clinical and Bacteriological Findingscontrasting
confidence: 63%
See 2 more Smart Citations
“…In the current study, the data on clinical remission parameters (Table 3) indicate that a single dose of ceftriaxone administration is superior to multiple doses of enrofloxacine for 14 days. Although 91.4% and 93.9% of uropathogens from dogs with uncomplicated urinary tract infections were susceptible to enrofloxacine and amoxicillin, respectively, the rate of clinical cure in response to the administration of these agents was lower than the values from susceptibility test (Westropp et al 2012). In this study, isolated uropathogens were sensitive to both enrofloxacine and ceftriaxone with no significant differences identified between clinical and microbiological cures.…”
Section: Pre-treatment Clinical and Bacteriological Findingscontrasting
confidence: 63%
“…Dogs with uncomplicated LUTI are usually treated for 10−14 days (Grauer 2009;Weese 2011). However, only a few publications dealing with the efficacy of short term antibiotherapy in dogs with uncomplicated LUTI are available (Westropp et al 2012;Clare 2014). The efficacy of short duration-high dose enrofloxacine treatment was tested in dogs with uncomplicated urinary tract disease (Westropp et al 2012).…”
Section: Pre-treatment Clinical and Bacteriological Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…As fluorquinolonas são a classe antimicrobiana de maior utilização nas ITUs por seu amplo espectro de atividade contra as altas concentrações de uropatógenos (Westropp et al, 2012). Entretanto, a prevalência de resistência as fluorquinolonas pelos uropatógenos urinários tem aumentado nos Estados Unidos da América (Ball et al, 2008).…”
Section: Introductionunclassified
“…Whilst the conventional view has been that the majority of bacterial cystitis episodes resolve with a 7-14 day course of oral antimicrobials, it is now apparent that assumption of microbiologic cure may be ill advised. Two recent studies comparing short-duration treatment with trimethoprim-sulfamethoxazole (Clare et al, 2014) or enrofloxacin (Westropp et al, 2012) with longer duration treatment with beta-lactam antimicrobials revealed that urine of dogs frequently returns to a culture-positive state posttreatment. Persistent or recurrent urinary tract infections can involve refractory bacterial isolates…”
Section: General Introductionmentioning
confidence: 99%